1996
DOI: 10.1152/ajpcell.1996.271.1.c304
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of activated protein kinase C contributes to downregulation by bryostatin

Abstract: We show that bryostatin 1 (Bryo) rapidly produces an inactive, incompetent 76-kDa form of protein kinase C-alpha (PKC-alpha) in the LLC-MK2 line of renal epithelial cells. Bryo, like phorbol 12-myristate 13-acetate (PMA), acutely activated PKC, as indicated by autophosphorylation and translocation of PKC-alpha, the predominant PMA-sensitive isoform expressed by the cells. Bryo concomitantly increased the 32P labeling of 80-kDa PKC-alpha by autophosphorylation and produced a 76-kDa form of PKC-alpha that lacked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
5
51
0
Order By: Relevance
“…A previous study showed that Bryo-1 substantially regulated PKC-␣, -␦, and -⑀ in NIH mouse fibroblast cells, whereas PMA did not distinguish between these isozymes (40). Other studies showed that Bryo-1 down-regulates PKC-␣ in epithelial cells and PKC-␣ and -␤ in human T cells (41,16). Bryo-1 also induces a unique biphasic response in PKC-␦, depending on concentrations leading to its degradation in NIH mouse fibroblast cells, B16F10 melanocytes, and HeLa cells (40,42,43).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study showed that Bryo-1 substantially regulated PKC-␣, -␦, and -⑀ in NIH mouse fibroblast cells, whereas PMA did not distinguish between these isozymes (40). Other studies showed that Bryo-1 down-regulates PKC-␣ in epithelial cells and PKC-␣ and -␤ in human T cells (41,16). Bryo-1 also induces a unique biphasic response in PKC-␦, depending on concentrations leading to its degradation in NIH mouse fibroblast cells, B16F10 melanocytes, and HeLa cells (40,42,43).…”
Section: Discussionmentioning
confidence: 97%
“…Extensive evidence points to proteolytic degradation as a major mechanism for desensitization of PKC signaling following prolonged activation. A widely accepted desensitization pathway involves proteasomal degradation of dephosphorylated protein that has accumulated in an intracellular detergent-insoluble compartment, with priming site dephosphorylation being the rate-limiting step for degradation (4,11,14,26,30,31,36,38,40). Although our findings confirm the existence of this pathway for endogenous PKC␣, the data point to the fully phosphorylated form of the activated protein as a major target for degradation in multiple cell types.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the endogenous activators of PKC, diacylglycerol, and Ca 2ϩ are only transiently elevated following agonist stimulation, only a small population of PKC may undergo dephosphorylation at a given time. The accumulation of dephosphorylated PKC is more readily observed with long lasting pharmacological treatments such as those from phorbol esters or the anti-cancer drug bryostatin (32).…”
Section: Discussionmentioning
confidence: 99%